Implementation of Google Play Billing (GPB) for Indonesian Developers and Consumers based on Law No. 5 of 1999 Concerning Monopoly Practices - Suhanda, Ariq Naufal Attalah; Tarina, Dwi Desi Yayi (Law Development Journal, 2024)
This study aims to analyze the Google Play Billing (GPB) policy implemented by Google towards developers and consumers in Indonesia in the context of Law No. 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition. This policy requires developers to use the Google Play Store internal payment system with a commission rate of 15-30%. This policy is considered to limit the freedom of developers in determining monetization methods and suppress their competitiveness, especially for small developers who have limited resources. The research method used is normative juridical with a statutory approach and case studies. Data were collected from regulations, official documents, and literature reviews. The analysis was carried out on relevant regulations and related legal cases, such as case 03/KPPU-I/2024 which is currently being handled by the KPPU. The results of the study show that the GPB policy has the potential to violate the principles of fair business competition, especially regarding abuse of dominant position and conditional sales practices (tying). This policy also creates barriers to market entry for new developers and limits the choice of payment methods for consumers, which has an impact on high prices for digital services and reduced innovation and diversity of applications. The conclusion of this study confirms the need for strong regulatory intervention to ensure a fairer, more transparent and competitive digital ecosystem. The novelty of this study is an in-depth analysis of the relevance of GPB policies to the legal framework for competition in Indonesia and policy recommendations that support local innovation and consumer protection.